2021
DOI: 10.3991/ijet.v16i16.23207
|View full text |Cite
|
Sign up to set email alerts
|

Applying Collaborative Learning for Enhancing the Teaching-Learning Process in Online Learning through Social Media

Abstract: The education system has experienced a significant paradigm change in the present pandemic situation. Traditional teaching methods, used as a marvel, will no longer function in the current situation. This shifting paradigm has affected higher education greatly, primarily because of the rapid movement from conventional approaches to advanced and creative online learning strategies. Collaborative learning is one of the most common ways of working and responding to current needs. This study deals with the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…For the review of literature, several sources like Educational Research Surveys, some published journals and relevant websites have been searched. Kurni, M., & K, S. (2021) [6] in their paper "Applying Collaborative Learning for Enhancing the Teaching-Learning Process in Online Learning through Social Media", found that Collaborative learning is about learning in communities organised to achieve educational objectives. In this research, WhatsApp, a typical social networking application, is used to create learner groups.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…For the review of literature, several sources like Educational Research Surveys, some published journals and relevant websites have been searched. Kurni, M., & K, S. (2021) [6] in their paper "Applying Collaborative Learning for Enhancing the Teaching-Learning Process in Online Learning through Social Media", found that Collaborative learning is about learning in communities organised to achieve educational objectives. In this research, WhatsApp, a typical social networking application, is used to create learner groups.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…También, es una forma de organización o labor donde un grupo de personas interactúan para ampliar sus conocimientos y competencias. Asimismo, consiste en establecer una red de saberes y habilidades para que las experiencias personales converjan como una sola, es decir, donde las personas generen un vínculo productivo que les permita tener un nivel apropiado de ideas y facultades (Kurni & Saritha, 2021).…”
Section: Aprendizaje Colaborativounclassified
“…Social networks, as an example of social media applications, enhance creativity and innovation among university students and allow for greater interaction between them [13]. The outcomes are a better collaborative work [14] and access to an endless number of training resources to be promoted [15]. Thus, social media becomes an interesting tool to promote digital learning with students [16] and also as a pedagogical resource for teachers [17].…”
Section: Technocreativity Digital Ecosystem and Entrepreneurshipmentioning
confidence: 99%